A dual porosity model of high-pressure gas flow for geoenergy applications - Hywel Thomas (Canadian Geotechnical Journal, 2018)
This paper presents the development of a dual porosity numerical model of multiphase, multicomponent chemical–gas transport using a coupled thermal, hydraulic, chemical, and mechanical formulation. Appropriate relationships are used to describe the transport properties of nonideal, reactive gas mixtures at high pressure, enabling the study of geoenergy applications such as geological carbon sequestration. Theoretical descriptions of the key transport processes are based on a dual porosity approach considering the fracture network and porous matrix as distinct continua over the domain. Flow between the pore regions is handled using mass exchange terms and the model includes equilibrium and kinetically controlled chemical reactions. A numerical solution is obtained with a finite element and finite difference approach and verification of the model is pursued to build confidence in the accuracy of the implementation of the dual porosity governing equations. In the course of these tests, the time-splitting approach used to couple the transport, mass exchange, and chemical reaction modules is shown to have been successfully applied. It is claimed that the modelling platform developed provides an advanced tool for the study of high-pressure gas transport, storage, and displacement for geoenergy applications involving multiphase, multicomponent chemical–gas transport in dual porosity media, such as geological carbon sequestration.